The Role of Onion (Allium cepa) in Controlling Parasitic Diseases: a Mini Review - Kourosh Cheraghipour; Abdolrazagh Marzban; Behrouz Ezatpour *; Kobra Moradpour; Vahideh Heydari Nazarabad (Lorestan University of Medical Sciences, 2020)
Parasitic infection is not one of the major challenges of developing countries. Despite extensive research, finding an effective strategy to combat parasites still requires more knowledge. The appearance of drug resistance in parasite strains and the growing side effects of chemical drugs have raised the use of medicinal plants as antiparasitic agents in recent years. Onion is one of the advantageous vegetables whose role in restricting the growth of certain parasites has been confirmed in numerous studies.  It has been attempted in the present review article to discuss the antiparasitic effects of onions and their derivatives by reviewing recent studies.